2017
DOI: 10.1111/jfpp.13286
|View full text |Cite
|
Sign up to set email alerts
|

The effect of drying methods on the concentration of compounds in sage and thyme

Abstract: The aim of the study was to evaluate effects of three drying methods of thyme and sage. Collected herbs were dried: under natural conditions, at temperature of 35 °C/40 °C, and freeze‐dried. The material was tested on the essential oil content using Clevenger apparatus; chemical composition was determined using gas chromatography coupled to mass spectrometry (GC‐MS). Antioxidant activity was analyzed by determining the ability to neutralize the free radical 2,2′‐azino‐bis (3‐ethylbenzothiazoline‐6‐sulphonic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 48 publications
2
16
1
Order By: Relevance
“…Heating of peppermint above 34 • C may already promote a significant loss of essential oils. Similar observations in the case of sage dried within a comparable temperature range were made by Sellami et al [23], and by Sadowska et al [24] for sage and thyme. The results published by these authors indicate 0.3% to 0.26% loss of oil during convective drying at 45 • C compared to natural drying at a temperature of about 22 • C [23], and increase of said loss at drying temperatures between 35 and 40 • C by 0.23 mL•100 g −1 for sage, and 0.16 mL•100 g −1 for thyme.…”
Section: Resultssupporting
confidence: 85%
“…Heating of peppermint above 34 • C may already promote a significant loss of essential oils. Similar observations in the case of sage dried within a comparable temperature range were made by Sellami et al [23], and by Sadowska et al [24] for sage and thyme. The results published by these authors indicate 0.3% to 0.26% loss of oil during convective drying at 45 • C compared to natural drying at a temperature of about 22 • C [23], and increase of said loss at drying temperatures between 35 and 40 • C by 0.23 mL•100 g −1 for sage, and 0.16 mL•100 g −1 for thyme.…”
Section: Resultssupporting
confidence: 85%
“…Particularly, drying temperature directly influences the changes in the physicochemical properties of foods. Current drying methods include: (1) conventional drying, for example hot-air/oven drying [1][2][3][4][5][6], conventional/low temperature-air drying [6][7][8], vacuum/vacuum oven drying [5,6,[9][10][11], sun drying [6,9,12], under shade drying [9,13], heat pump-dehumidified air drying [2], low-pressure superheated steam drying [1], and freeze drying [2,5,9]; (2) radiation drying such as microwave drying [2,6,12,[14][15][16], infrared drying [3,4,6]; and (3) combined drying or novel drying, for instance, microwave-assisted hot-air drying [3], infrared-combined hot air drying [1,4], hot air-assisted radio frequency drying [3], vacuum-microwave drying [10,17], combined infrared-vacuum drying [18], and combined low-pressure superheated steam drying and far-infrared radiation [19]. Among these drying techniques, conventional drying is simpler, has lower production costs, but is less effective (except for freeze drying), while radiation and novel drying are effective but are more complicated, and have higher production costs.…”
Section: Introductionmentioning
confidence: 99%
“…Kruma et al (2008) reported that total phenolic compounds in latvian thyme were 74.96 mg/g. Sadowska et al (2017) evaluate the effects of three drying methods (under natural conditions, at temperature of 35 °C/40 °C, and freeze-dried) of thyme on some biochemical properties. According their result, the highest content of polyphenols for thyme was found at 35 °C drying.…”
Section: Total Phenols Contentmentioning
confidence: 99%